1976
DOI: 10.1038/bjc.1976.187
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, distribution and elimination of the cancerostatic lectins abrin and ricin after parenteral injection into mice

Abstract: Summary.-The survival time of mice after i.v. injection of the cancerostatic lectins, abrin and ricin, was recorded. The LD50 dose was found to be 10-13 ng and 55-65 ng per mouse for abrin and ricin, respectively. Increasing amounts of toxin reduced the survival time, reaching a minimum of about 10 h. Lactose injected with ricin, provided partial protection against ricin, as measured by the survival time.Abrin and ricin labelled with 1251, and shown to retain their full toxic activity, were injected into mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 10 publications
(3 reference statements)
5
58
0
Order By: Relevance
“…Since several studies have demonstrated the antitumour properties of ricin (Lin et al, 1970;Fodstad et al, 1976Fodstad et al, , 1977Fodstad & Pihl, 1978), preliminary experiments were carried out to evaluate its effect on M-MSV-induced tumour growth. Tumour-bearing irradiated mice, receiving M-MSV in the rear footpad 5 to 6 days previously, were injected i.v.…”
Section: Antitumour Activity Of Ricin-treated T-lymphocyte Transfermentioning
confidence: 99%
“…Since several studies have demonstrated the antitumour properties of ricin (Lin et al, 1970;Fodstad et al, 1976Fodstad et al, , 1977Fodstad & Pihl, 1978), preliminary experiments were carried out to evaluate its effect on M-MSV-induced tumour growth. Tumour-bearing irradiated mice, receiving M-MSV in the rear footpad 5 to 6 days previously, were injected i.v.…”
Section: Antitumour Activity Of Ricin-treated T-lymphocyte Transfermentioning
confidence: 99%
“…When injected intravenously into rats or mice, rich rapidly accumulates in the liver and, to a lesser extent, in the spleen [5] wise be cleared from the bloodstream in animals and prompted us to devise ways of modifying the carbohydrate side chains in the toxin to prevent hepatic recognition. A previous attempt by Simeral et al [8] to destroy the carbohydrate in ricin using sodium metaperiodate resulted in virtually complete loss of toxicity.…”
mentioning
confidence: 99%
“…Cells resistant to abrin and ricin were isolated as surviving clones of X-ray irradiated HeLa. cells grown in the presence of 1 pg/ml of abrin or ricin [7].…”
Section: Methodsmentioning
confidence: 99%